High heat transfer using hybrid engine coolant - Devarajan, Ramasamy; Sandhya, Madderla; Kumaran, Kadirgama; Mahendran, Samykano; Sudhakar, Kumarasamy; Md. Mustafizur, Rahman; Wan Sharuzi, Wan Harun (2021)
To develop a stable nanofluid based on water & ethylene glycol by using nanoparticles graphene and crystal nano cellulose (cnc) and analyze the characteristic properties and the thermo-physical properties of water & ethylene glycol-based graphene/cnc hybrid nanofluids and evaluate the heat transfer performance of the newly developed hybrid nanofluid in a radiator